Cause of Early Failure of Laser Hemorrhoidoplasty with Mucopexy in 3rd and 4th Degree Hemorrhoids at Shifa Hospital Saidu Sharif Swat - Hunain, Shamsher Ali, Uzma, Mahboob Ahmad Khan, Adnan Ishaq (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose of Study: Common surgical approaches in the management of hemorrhoid disease such as standard Milligan Morgan hemorrhoidectomies are with severe postoperative pain and long recovery time. Studies aimed to perform laser hemorrhoidoplasty (LHP) in patients with symptomatic hemorrhoidal disease show less pain and early return to work. But some time LHP with mucopexy fails. My study is designed to search out the cause of early failure of LHP with mucopexy in 3rd degree and 4th degree hemorrhoidal disease at Shifa Hospital Saidu Sharif Swat. Methods: In our study 65 patients with 3rd and 4th degree hemorrhoids were retrospectively included for LHP with mucopexy. Outcomes such LHP and mucopexy failure with in first ten days and its causes were evaluated by Digital rectal examination and external examination. After counselling patients, they were called back for follow-up after 6 weeks and examination under anesthesia was carried out. Results: Out of 65 patients 3 patients came with early prolapse of hemorrhoid pedicle and pain although 62 patients had no prolapse after LHP with mucopexy with mild pain in first ten days. Among those who came back with early prolapse after LHP with mucopexy one patient came on 3rd post op day the second and third patients came on 5th post op day with lump coming out of anus. On external examination and DRE it was noticed that the stich taken up for mucopexy was visible detached from the mucosa at the pedicel level. So, after proper counselling and analgesic use these patients were called back after 6 weeks and were put back for examination under anesthesia and LHP with mucopexy was done again in the prolapsed part. Further they were called back at 10th day and after 6 weeks and there was no evidence of prolapse or other complication. Conclusion: This study demonstrates disruption of suture after mucopexy with laser application as a cause of early failure after LHP with mucopexy. The most probable cause of this suture disruption seems to be the firing of laser too close to the stitch. In order to prevent this disruption of suture it is better to fire laser at least one centimeter away from the stich site and to avoid excessive firing. Keyword: Hemorrhoids, laser, hemorrhoidoplasty, mucopexy hemorrhoidectomy.